2020
DOI: 10.1142/s0219633620500169
|View full text |Cite
|
Sign up to set email alerts
|

Ab-initio binding of barnase–barstar with DelPhiForce steered Molecular Dynamics (DFMD) approach

Abstract: Receptor–ligand interactions are involved in various biological processes, therefore understanding the binding mechanism and ability to predict the binding mode are essential for many biological investigations. While many computational methods exist to predict the 3D structure of the corresponding complex provided the knowledge of the monomers, here we use the newly developed DelPhiForce steered Molecular Dynamics (DFMD) approach to model the binding of barstar to barnase to demonstrate that first-principles m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…To overcome such limitations, a hybrid method involving DelPhi [ 48 , 49 , 50 , 51 ] (a popular Poisson–Boltzmann equation solver) and steered MD was developed. The method, termed DelPhi–Force MD (DFMD) [ 10 , 52 ], was successfully applied to dock substrates to an enzyme [ 2 ] and a biomolecule onto another biomolecule (such as barstar onto barnase) [ 10 ]. It was demonstrated that such an approach allows one to take advantage of the MD protocol to sample different conformations while simultaneously adding electrostatic force-based guidance of the ligand toward the correct binding pocket/interface [ 2 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
See 3 more Smart Citations
“…To overcome such limitations, a hybrid method involving DelPhi [ 48 , 49 , 50 , 51 ] (a popular Poisson–Boltzmann equation solver) and steered MD was developed. The method, termed DelPhi–Force MD (DFMD) [ 10 , 52 ], was successfully applied to dock substrates to an enzyme [ 2 ] and a biomolecule onto another biomolecule (such as barstar onto barnase) [ 10 ]. It was demonstrated that such an approach allows one to take advantage of the MD protocol to sample different conformations while simultaneously adding electrostatic force-based guidance of the ligand toward the correct binding pocket/interface [ 2 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
“…It was demonstrated that such an approach allows one to take advantage of the MD protocol to sample different conformations while simultaneously adding electrostatic force-based guidance of the ligand toward the correct binding pocket/interface [ 2 ]. Moreover, it was shown that DFMD can successfully dock to barnase even if the initial positions and orientations of both are completely different from the correct ones [ 10 ].…”
Section: Electrostatics Of Wild-type Biological Macromoleculesmentioning
confidence: 99%
See 2 more Smart Citations